Current estimates of the incidence of acute venous thromboembolic disease in Canada: A meta-analysis. Issue 197 (January 2021) - Payne, James G.; Tagalakis, Vicky; Wu, Cynthia; Lazo-Langner, Alejandro
Abstract: Background: Venous thromboembolism (VTE) is a significant public health concern that carries high rates of morbidity and mortality. To date, limited epidemiological data are available. We conducted a meta-analysis of three epidemiological studies in Canada to determine an estimate of the national VTE incidence rate. Methods: We used data from three large studies that looked at acute VTE incidence in three of Canada's largest provinces. Patients in each of the concurrent studies were identified using various provincial health databases. Patients with previous diagnosis of VTE (prevalent VTE) were excluded. Age- and sex-specific data were combined using a generic inverse variance method to produce an estimate for the total VTE incidence rate for the three provinces, as well as estimates by age group and sex. Results: Studies included 113, 171, 431 patient-years of observation and 144, 906 newly diagnosed VTE events. The meta-analysis resulted in a combined incidence rate (IR) of 1.29 acute VTE events per 1000 person-years (95% CI 1.06–1.53). Among men (55, 415, 674 observed person-years and 63, 246 events), the IR was 1.13 (95% CI 0.91–1.36), and among women (57, 755, 755 observed person-years and 81, 660 events) it was 1.44 (95% CI 1.19–1.69). Higher VTE incidence was observed in females and the IR consistently increased with age. Conclusion: This study provides a current estimate of VTE incidence in Canada. The results were in line with estimates obtained from studies in other jurisdictions and confirming higher incidence of VTE in females and in the elderly. Highlights: Meta-analysis of three provincial population-based studies in Canada Studies included 113, 171, 431 patient-years of observation and 144, 906 newly diagnosed VTE events. VTE incidence rate 1.29 acute VTE events per 1000 person-years (95% CI 1.06–1.53). Sex-specific male IR 1.13 (95% CI 0.91–1.36) and female IR 1.44 (95% CI 1.19–1.69). Incidence increases with age in both males and females.